If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -127 = 4x + 169 Reorder the terms: -127 + 12x = 4x + 169 Reorder the terms: -127 + 12x = 169 + 4x Solving -127 + 12x = 169 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -127 + 12x + -4x = 169 + 4x + -4x Combine like terms: 12x + -4x = 8x -127 + 8x = 169 + 4x + -4x Combine like terms: 4x + -4x = 0 -127 + 8x = 169 + 0 -127 + 8x = 169 Add '127' to each side of the equation. -127 + 127 + 8x = 169 + 127 Combine like terms: -127 + 127 = 0 0 + 8x = 169 + 127 8x = 169 + 127 Combine like terms: 169 + 127 = 296 8x = 296 Divide each side by '8'. x = 37 Simplifying x = 37
| (8x^4-2x^2+3x-5)-(2x^4+x^3+3x+5)= | | (3x+3)+(15-3x)= | | 7(2n+2)=7(7n+7)+9 | | 4(q)+(-1)(1-q)=1(q)+2(1-q) | | -4n(6n-5)+3n= | | 5(x+3)=4x+14 | | 0.9x-5.3=0.1 | | (9x-6)+6= | | 2+-6m=-4m+10 | | -9(y-1)=2-8y | | -3x(x+5)-7=-8+10 | | 3a-(5-3a)=10 | | 4(q)+(-1)(1-q)=1q+2(1-q) | | 5x+-6=3x+-8 | | (3-x)+(x-4)=2(x+4) | | w=-125t+6000 | | -6+5(-9x-3)=-10 | | -6+(-9x-3)=-10 | | 24+r=28 | | 5p+8=-32 | | 2=-19+z | | 6m-4=4m | | 2=-4+k | | 18p^3-63p^2-9p=0 | | 4x^2+8x+48y-44=0 | | -7(2x-8)+3=-14x+59 | | 10-4=16 | | Q-3=25 | | F(x)=ln(x)*x^2 | | 66=10-8b | | K-12=11 | | b/2=-7 |